Risk prioritization - Tools and recent methodologies - Skandamis P.N. (Food safety challenges for mediterranean products, 2015)
Risk profile is the first step of stochastic quantitative process risk models, by identifying the potential pathogen-matrix combinations of safety concern, then enabling the risk ranking of these combinations. This in turn may assist food industries about existing or emerging food safety issues and the authorities (risk managers) in making informed decisions on further commissioning a systematic quantitative risk assessment to address public health concerns. Risk ranking can be based on a variety of criteria, associated with exposure to and the severity of a hazard. Among the most recent and popular ones is the Disability or Quality Adjusted Lost Years (DALYs), which assesses the relative impact of different diseases based on incidence rate, cost of illness, hospitalizations and deaths. There is also a great number of tools for risk ranking publicly available either in the form of XL-based software (e.g., Risk Ranger) or as web-based platform (e.g., iRisk). As a follow up, there has been an increasing trend of developing strategies for prioritizing risks based on critical questions addressing all the aforementioned issues. A detailed list of such approaches is appended here and advantages or the concerns for a universally accepted methodology are discussed.
Workshop Food Safety Challenges for Mediterranean Products, 2014/06/10-11, Zaragoza (Spain)